CLINICAL MARGINAL FIT AND PATIENT S PREFERENCES IN IMPRESSION TECHNIQUE USING DIGITAL INTRAORAL SCANNER VERSUS POLYVINYLSILOXANE MATERIAL - Nawapat Sakornwimon (Chulalongkorn University, 2015)
75 pages